Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/cdev.12571
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Secure Base Script Knowledge and the Developmental Construction of Attachment Representations

Abstract: Increasing evidence suggests that attachment representations take at least two forms—a secure base script and an autobiographical narrative of childhood caregiving experiences. This study presents data from the first 26 years of the Minnesota Longitudinal Study of Risk and Adaptation (N = 169), examining the developmental origins of secure base script knowledge in a high-risk sample, and testing alternative models of the developmental sequencing of the construction of attachment representations. Results demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(114 citation statements)
references
References 67 publications
9
82
4
1
Order By: Relevance
“…Although the ASA was developed for use with adults (Waters & Rodrigues-Doolabh, 2001), other prompt-word sets have been developed for use with children. The middle childhood version of the ASA (Waters, Fraley, et al, 2015) consists of three prompt word outlines featuring mother-child dyads: Scary Dog in the Yard, At the Beach, and Soccer Game.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ASA was developed for use with adults (Waters & Rodrigues-Doolabh, 2001), other prompt-word sets have been developed for use with children. The middle childhood version of the ASA (Waters, Fraley, et al, 2015) consists of three prompt word outlines featuring mother-child dyads: Scary Dog in the Yard, At the Beach, and Soccer Game.…”
Section: Methodsmentioning
confidence: 99%
“…To date, studies examining processes related to secure base script development have primarily focused on acquisition rather than on organization or elaboration. For example, the origins of secure base script knowledge have been well documented with studies finding significant links between script knowledge and parenting quality across childhood in normative‐risk, high‐risk, and genetically unrelated parent–child dyads (Schoenmaker et al., ; Steele et al., ; Vaughn et al., ; Waters, Ruiz, & Roisman, ). Although it is clear that sensitive care plays an important role in the construction of attachment representations, questions pertaining to how secure base script knowledge is organized, generalized, and elaborated have gone mostly unexamined.…”
mentioning
confidence: 99%
“…Both Dykas et al (2006) and Steele et al (2014) found that adolescent ASA script scores were significantly correlated with established measures of adult attachment (e.g., Adult Attachment Interview, AAI, George et al, 1985; Experiences in Close Relationships–Revised questionnaire, ECR-R, Fraley et al, 2000) and had similar patterns of associations with parental sensitivity measures from infancy through early adolescence and early attachment histories as did scale scores derived from the AAI completed by these SECCYD participants. Schoenmaker et al (2015) also reported significant associations between maternal sensitivity, assessed during infancy and again at seven years of age, and attachment security at age 23, assessed using the ASA (see also Waters, Ruiz, & Roisman, in press). …”
mentioning
confidence: 88%
“…Based on these expectations, we predicted that mothers with high script scores (ASA) would receive higher co-construction scores on both of our tasks. In light of work demonstrating that secure AAI narratives include significant secure base script knowledge, we also anticipated similar relations with AAI coherence scores (Waters, Ruiz, & Roisman, 2017).…”
Section: The Current Studymentioning
confidence: 76%